EXPLORING TEACHERS’ PROFESSIONAL IDENTITY THROUGH MOTIVATION AND COMMITMENT TO TEACHING - Pires, Sidónio António (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2023)
The study aimed to explore teachers’ professional identities through motivation and commitment to teaching. It highlights teachers’ initial and sustaining motivation that shapes their professional identity. The study also focuses on how teachers’ commitment to teaching forms their identity. The study intended to provide an answer to the research question, of how motivation and commitment shape the three teachers’ professional identities in teaching. The study applied the document research method, where the researcher used three documentary videos from three teachers namely Robin, Vanday, and Imoto as the source of the data. For the data collection, the researcher watched and transcribed the speech from each video and coded it according to each category. The findings reveal that the three teachers’ motivation significantly boosts their productivity due to their self-efficacy, personal experience within society, and passion to teach the students, their love and concern for the students. The findings for commitment reveal that teachers’ independence, competence, and connectedness play important roles for teachers to be committed in teaching. This study implies that motivation and commitment play key roles in teachers’ professional identity.